HISTORY AND METHODOLOGY OF BIOGEN TECHNOLOGIES (ONTOLOGICAL-EPISTEMOLOGICAL ANALYSIS) - Shermanov Isobek Chilmamatovich (European Journal of Humanities and Educational Advancements, 2023)
The article examines the dynamics of development in the fields related to biogenic technology, and it is necessary to master the methodology of application in social activities with a scientific approach to the concepts of human artificial and natural intelligence. The biotechnological factor is one of the spheres of the country’s development, and the history, present and future of this process is scientifically based on ontological and epistemological analysis.